Exploring Individual and Interpersonal Factors of Personal Identifiable Information on Social Networking Sites - Alturki , Ahmed; Alkhaldi, Shatha; Algarni , Abdullah (Advances and Challenges in Science and Technology Vol. 5, 2023)
This study attempts to investigate the effects of interpersonal and individual characteristics on "personal identifiable information" (PII) disclosure, including the desire for self-validation, social skills, and readiness to trust others. Quantitative research techniques were applied in the study. Saudi Arabia provided 375 male and female volunteers for the research. The information was gathered via a closed-ended survey, and SPSS version 23 was utilized for analysis. The findings indicate the role of self-validation, public self-consciousness, willingness to trust others, and social skills as influential determinants, affecting the extent of PII disclosure on SNS. The outcomes, generated from Principal Component Analysis, elucidate six salient facets with eigenvalues equal to or exceeding one. Notably, factor loadings in proximity to 1 indicate a more robust association, underscoring significant correlations within the data. These revelations offer a comprehensive framework for understanding the multifaceted landscape of PII disclosure, thereby advancing our comprehension of online information-sharing behavior.